O impacto dos gastos públicos no crescimento econômico do Brasil (1995 a 2011) - Costa, Daniel Sousa (2019)
The main objective of this study is to analyze the impact of public spending on economic growth in Brazil, controlling for determinants of educational level and income inequality. The period from 1992 to 2011 was analyzed, having as dependent variable the per capita GDP of all the federative units. To represent public expenditures, an aggregate public expenditure index (PGI) was created using the multivariate Principal Components Analysis (PCA) technique. The econometric modeling used was panel data and the regression was estimated by Fixed Effects corrected the effects of heteroscedasticity and autocorrelation. Among the main results obtained, a positive and significant relationship was found between public spending and economic growth. The other determinants investigated play an important role in the trajectory of economic growth in Brazil, highlighting the income inequality that had the greatest impact. Thus, policies aimed at deconcentraiting income, increasing educational attainment, and the effective use of public spending can yeld positive results in a country’s economic growth.